Pengaruh Kampanye Negatif dan Kampanye Hitam terhadap Pilihan Pemilih pada Pemungutan Suara Ulang (PSU) Pemilihan Walikota dan Wakil Walikota Pekanbaru Tahun 2011 - Ali Yusri; Adlin (Nakhoda: Jurnal Ilmu Pemerintahan, 2012)
Negative campaigning and a black campaign in order to win the general election is very common in manycountries including Indonesia. Negative campaigning and a black campaign in the form of the issue of uglinessand disadvantages of each candidate occurs before the implementation of the PSU and published in variouslocal media that it becomes a little more information would influence voters in their choice. This study aims toreveal the extent of the influence of negative campaign against voters in their choice at PSU election of Mayorand Deputy Mayor of Pekanbaru in 2011. This study uses quantitative methods to multistage random samplingtechnique to draw the 120 survey respondents are spread across six districts in the city of Pekanbaru. The Datawere taken through a questionnaire enclosed further analyzed and presented in the form of frequency tables andcrosstable. The results showed the majority of respondents chose a particular candidate because of too manynegative issues other candidates. A Couple of Septina-Muluk Erizal were not elected by voters due to thenegative issues that get fixed on Septina many negative issues such as allegations of power greedy, want topreserve the family's power (political dynasty) and the negative stigma that women should not be leaders.